A Routing Model for Hybrid Hub-and-Spoke with Time Windows - Felix Arya Gunadi; Dharma Lesmono; Kinley Aritonang (Jurnal Teknik Industri, 2020)
Currently, the company competition is getting tighter. Distribution companies need to provide excellent service to their customers to maintain their competitiveness. Distribution service performance could be measured with lead time. However, Reducing lead times may increase costs. This problem could be solved using freight consolidation and reducing backhaul. Freight consolidation can be done by using a hub-and-spoke network with a combination of inbound and outbound distribution. This study developed a route model for hybrid hub-and-spoke with time windows. This model determined the routes for shipping goods to consumers and taking products to suppliers using the same vehicle to reduce the backhaul. This model also conducted freight consolidation at the hub. The decision variables in this model included the routes of delivery to consumers, the collection of goods at the suppliers, the number of products distributed through the hub and direct shipping, and the excellent distribution route. This model was implemented into the problems. Besides, a sensitivity analysis of the model was carried out.